2003
DOI: 10.1103/physrevlett.90.066102
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Thiolates to Singly Coordinated Sites on Au(111) Evidenced by Photoelectron Diffraction

Abstract: The adsorption structure of methylthiolate (CH3S) adsorbed on Au(111), a long-standing controversial issue, has been unambiguously determined by scanned-energy and scanned-angle S 2p photoelectron diffraction. The methylthiolate molecules are found to occupy atop sites with a S-Au distance of 2.42 +/- 0.03 A. The angular distribution of the S 2p photoelectrons due to forward scattering reveals that the S-C bond is inclined by approximately 50 degrees from the surface normal towards both the [211] and [121] (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
203
4
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(238 citation statements)
references
References 21 publications
27
203
4
4
Order By: Relevance
“…Presumably, this could be induced by dominant intermolecular interactions of nitrosoarene residues within the molecular layer leading to occupation of different adsorption sites of the Au(111) lattice by S atoms. As it is known from the literature, the geometric height difference between various adsorption sites of sulfur atoms on an Au(111) lattice is about 0.02 nm, 43 which is in good agreement with measured corrugation. The periodicity of the superstructure of 1.5 nm corresponds very well to 3 3 times that of the Au(111) lattice (a = 0.29 nm) indicating a 3 3 3 3  molecular arrangement, same as for SAMs of nitrosoarene derivatives studied in our recent paper.…”
Section: Self-assembled Layers On An Au(111) Surfacesupporting
confidence: 73%
“…Presumably, this could be induced by dominant intermolecular interactions of nitrosoarene residues within the molecular layer leading to occupation of different adsorption sites of the Au(111) lattice by S atoms. As it is known from the literature, the geometric height difference between various adsorption sites of sulfur atoms on an Au(111) lattice is about 0.02 nm, 43 which is in good agreement with measured corrugation. The periodicity of the superstructure of 1.5 nm corresponds very well to 3 3 times that of the Au(111) lattice (a = 0.29 nm) indicating a 3 3 3 3  molecular arrangement, same as for SAMs of nitrosoarene derivatives studied in our recent paper.…”
Section: Self-assembled Layers On An Au(111) Surfacesupporting
confidence: 73%
“…From recent photoelectron diffraction data and X-ray standing wave analysis it was concluded, however, that thiolate molecules favor the on-top adsorption sites, where a sulphur atom is positioned on top of a single Au atom of the substrate [48,49].…”
Section: Structuresmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Various groups have studied the dissociative adsorption of dimethyl disulfide (DMDS) on Au(111), both theoretically 3,11 and experimentally. [13][14][15] In particular, Nuzzo et al 13 suggested, after employing a large variety of experimental methods including X-ray photoelectron spectroscopy (XPS), Auger electron spectroscopy (AES), high-resolution electron energy loss spectroscopy (HREELS), and thermal desorption spectroscopy (TDS), that the breaking of the (weak) S-S bond of DMDS leads to the formation of a) Electronic mail: barmparis@materials.uoc.gr. two methanethiolate-surface bonds on Au(111) at low coverage.…”
Section: Introductionmentioning
confidence: 99%